Auditor Characteristics and Financial Reporting Fraud Risk - behzad yazdani; Zahra Lashgari; Fazel Mohammadi node (پژوهش‌های تجربی حسابداری, 2022)
Fraud risk assessment is an integral part of audit process, which is reviewed continuously until the end of the audit process because auditors are responsible for the type, manner, and extent of procedures used in the audit process to hedge fraud risk. Therefore, their own characteristics can influence the process of fraud risk assessment. The purpose of this study is to evaluate the characteristics of auditors to reduce the risk of fraud in corporate financial reporting. The sample consists of 87 firms listed in Tehran Stock Exchange during the years 2011-2018, being surveyed in a descriptive-correlational manner using Logit regression. The results show that, in firms with a longer audit tenure, as well as in firms with auditors specialized in industry, the risk of fraud is more likely; however, in firms audited by large companies, risk of fraud is less likely.